Detection of explosive atmospheres using the software atmosxp v2.0 (2014)
The conditions of explosive atmospheres and accumulation of gases within underground coal mines require a detailed analysis and the development of models and mechanisms that allow their detection. For this purpose we have developed the software AtmosXp V2.0 which includes the diagram of Coward for the analysis of these explosive mixtures.